The pivotal role of tertiary lymphoid structures in the tumor immune microenvironment - Liu, Chengsen; Cao, Jiandong (Frontiers in Oncology, 2025)
Tertiary lymphoid structures (TLS) are ectopic lymphoid structures that form in non-lymphoid tissues in response to chronic inflammatory stimulation. Structurally and functionally resembling lymph nodes, TLS are primarily composed of B cells, T cells, dendritic cells, and other immune cell populations. Critically, TLS serve as direct sites for initiating anti-tumor immune responses. Within tumors, TLS facilitate the accumulation of immune cells—particularly effector subsets such as cytotoxic T cells and antibody-producing B cells—in the tumor microenvironment, thereby establishing a localized hub for both cellular and humoral immunity. This localized immune activation correlates with improved patient prognosis and enhanced responses to immunotherapy. In this review, we summarize the organization, formation drivers, detection markers, and the interplay between TLS and tumor-associated genes. Furthermore, we discuss the potential of TLS as biomarkers for immunotherapy efficacy and their translational clinical applications.